The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.bmcl.2015.07.090
|View full text |Cite
|
Sign up to set email alerts
|

Boronic acid-containing aminopyridine- and aminopyrimidinecarboxamide CXCR1/2 antagonists: Optimization of aqueous solubility and oral bioavailability

Abstract: The chemokine receptors CXCR1 and CXCR2 are important pharmaceutical targets due to their key roles in inflammatory diseases and cancer progression. We have previously identified 2-[5-(4-Fluoro-phenylcarbamoyl)-pyridin-2-ylsulfanylmethyl]-phenylboronic acid (SX-517) and 6-(2-boronic acid-5-trifluoromethoxy-benzylsulfanyl)-N-(4-fluoro-phenyl)-nicotinamide (SX-576) as potent non-competitive boronic acid-containing CXCR1/2 antagonists. Herein we report the synthesis and evaluation of aminopyridine and aminopyrimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…SX-517 was eventually replaced with a new lead compound SX-576 ( Table 5 ), which had greater systemic exposure, greater inhibition in vitro, increased metabolic stability, and improved pharmacokinetic properties in vivo [ 127 ]. Lastly, a structure-activity relationship (SAR) study was conducted to create an orally available compound with improved aqueous solubility with the same activity level as SX-576 [ 128 ]. The third-generation compound that was synthesized not only met the desired results, it was also able to significantly reduce the influx of neutrophils [ 128 ].…”
Section: Boron Medicinal Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…SX-517 was eventually replaced with a new lead compound SX-576 ( Table 5 ), which had greater systemic exposure, greater inhibition in vitro, increased metabolic stability, and improved pharmacokinetic properties in vivo [ 127 ]. Lastly, a structure-activity relationship (SAR) study was conducted to create an orally available compound with improved aqueous solubility with the same activity level as SX-576 [ 128 ]. The third-generation compound that was synthesized not only met the desired results, it was also able to significantly reduce the influx of neutrophils [ 128 ].…”
Section: Boron Medicinal Chemistrymentioning
confidence: 99%
“…Lastly, a structure-activity relationship (SAR) study was conducted to create an orally available compound with improved aqueous solubility with the same activity level as SX-576 [ 128 ]. The third-generation compound that was synthesized not only met the desired results, it was also able to significantly reduce the influx of neutrophils [ 128 ]. Boronic acid-substituted stilbenes have been investigated as ligands for transtherytin (TTR) to stabilize the homotetramer, preventing fibril formation that leads to amyloidosis [ 129 ].…”
Section: Boron Medicinal Chemistrymentioning
confidence: 99%
“…Furthermore, it was hypothesized that a replacement of the sulfur atom by another heteroatom might improve aqueous solubility and therefore improve oral bioavailability. 90 Several analogues were synthesized and screened for their potential as an intracellular Ca 2+ flux inhibitor. These efforts resulted in the discovery of SX-667 ( 39 , Fig.…”
Section: Discovery and Development Of Allosteric Intracellular Chemok...mentioning
confidence: 99%
“…Among nitrogen containing heterocycles, 2-aminopyridines have gained considerable interest for synthetic research groups due to their high impact applications into biological and material science fields. [1][2][3][4][5][6][7] Specifically, the 2-aminopyridine moiety is present in many pharmacologically and biologically important compounds, including nitric oxide synthases (NOS), 2,8 CXCR1/2, 9 and renin 10 inhibitors, displaying antifungal, [11][12][13] antiinflammatory, [11][12][13][14] analgesic, 11,14 antiparasitic, 15 antiviral, 16 antipyretic, and antimicrobial 17 properties. Recently, we focused on the preparation of bioactive nitrogen-containing heterocycles and we have shown that the synthesis of 2-aminopyridines from enaminolactone nitriles and primary aliphatic and aromatic amines was promising and constituted a valuable strategy.…”
Section: Introductionmentioning
confidence: 99%